THE IMPACT OF THE COVID-19 PANDEMIC ON THE RAIL TRANSPORT NETWORK IN POLAND - Ojdana-Kościuszko, Monika (Management and Administration Journal, 2022)
In this article the situation of Polish rail transport during the first and second waves of the COVID-19 pandemic is presented. Noticeable trends of rail transport usage are outlined. Basic parameters such as the number of passengers, the amount of goods transported indicators depicting the state of rail transport in 2020 and 2021 are shown. To learn about the issues, a review of the literature was used, i.e. compact items, scientific articles, and an analysis of statistical data from the Reports of the Railway Transport Office.